STUDI IMPLEMENTASI STANDAR PELAYANAN KEFARMASIAN DALAM PENGKAJIAN RESEP RACIKAN PEDIATRI DI RSUD LASINRANG KABUPATEN PINRANG - Nurlina, Nurlina; Reski Awalia; A. Hasrawati (Nusantara Hasana Journal, 2025)
Pediatrics is a group that is vulnerable to disease because the immune system and physiological functions of organs are not yet fully developed. Pediatric patients usually have multiple medication problems. Medication errors can occur in each treatment process, both in the prescribing process (prescribing), reading prescriptions (transcribing), preparation to delivery of drugs (dispensing), and in the process of using drugs (administration). The location of this research was at Lasinrang Hospital, Pinrang Regency based on the Regulation of the Minister of Health of the Republic of Indonesia No. 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals including administrative aspects, pharmaceutical aspects, and clinical aspects. The type of research used with descriptive non-experimental method with retrospective data collection, then observed based on administrative, pharmacetic, and clinical conformity. The results of the study in the administrative aspect showed 100% completeness, namely the patient's name, patient's age, patient's gender, doctor's name, doctor's address, prescription date, and prescription origin unit. The pharmacetic aspect showed 100% except for the strength of the drug 50.32% and the amount of the drug 31.04%. The clinical aspect showed 100% completeness of the accuracy of drug use. In terms of dose accuracy, there were drugs that were underdosed once 26.14% and daily 6.86%, right dose once 26.79% and daily 20.91%, exceeding the usual dose once 47.38% and daily 72.22%, and overdose once 11.76% and daily 31.69%.